2014
DOI: 10.1136/jmedgenet-2013-102045
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of hepatic expression quantitative trait loci (eQTLs) in a Han Chinese population

Abstract: BackgroundElucidating the genetic basis underlying hepatic gene expression variability is of importance to understand the aetiology of the disease and variation in drug metabolism. To date, no genome-wide expression quantitative trait loci (eQTLs) analysis has been conducted in the Han Chinese population, the largest ethnic group in the world.MethodsWe performed a genome-wide eQTL mapping in a set of Han Chinese liver tissue samples (n=64). The data were then compared with published eQTL data from a Caucasian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Given the nonsignificant association after Bonferroni correction for the locus‐wide eQTL mapping, we further validated the results in an additional hepatic eQTL data set published recently . Again, imputed and genotyped SNP data (k = 1,619 after QC) in the same region were used.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Given the nonsignificant association after Bonferroni correction for the locus‐wide eQTL mapping, we further validated the results in an additional hepatic eQTL data set published recently . Again, imputed and genotyped SNP data (k = 1,619 after QC) in the same region were used.…”
Section: Resultsmentioning
confidence: 61%
“…Given the nonsignificant association after Bonferroni correction for the locus-wide eQTL mapping, we further validated the results in an additional hepatic eQTL data set published recently. 22 Again, imputed and genotyped SNP data (k 5 1,619 after QC) in the same region were used. We found that, in this population, the SNPs in the LD block were strongly associated with the expression of FADS1 (10 28 < P < 10 26 ), but much more weakly with FADS2 (10 24 < P < 10 22 ), and no association with FADS3 (P > 0.05; Supporting Fig.…”
Section: Genome-wide Association Analyses Of Hepatic Contents Of Lipimentioning
confidence: 99%
“…[21,22] Meanwhile, a healthy diet and regular exercise may enhance the insulin sensitivity and glucose homeostasis, thereby reducing the incidence of NAFLD. [23] Genetic factors have also been considered to play a very important role in the NAFLD development, and multiple GWAS have discovered several genes, including TM6SF2, SAMM50, PARVB, and PNPLA3, [13,15] which are potential candidates for NAFLD susceptibility and progression. Among these genes, a strong association has been demonstrated between PNPLA3 polymorphisms and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…[15] As no study regarding the association of rs2896019 and rs3810622 and predisposition to NAFLD in other populations has yet been published, in this study, we will further evaluate the association of rs2896019 and rs3810622 polymorphisms in PNPLA3 gene with NAFLD based on a Han Chinese population, which represents the world's largest population, to further elucidate the genetic causes of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Liver is a critical organ for understanding drug metabolism, as well as coagulopathies and metabolic disorders, and is likely to be the causal tissue for many GWAS studies [12][13][14]. However, eQTL mapping in liver tissue has been primarily conducted in European and Asian populations [9,15,16]. Due to the difficulty in obtaining liver from African American (AA) donors, there are no studies performed exclusively in the liver of AAs, leaving the genome-wide regulation of gene expression in populations with high levels of African ancestry unexplored.…”
Section: Introductionmentioning
confidence: 99%